Quando AzMina falam: um estudo de caso sobre o jornalismo feminista, digital e interseccional na revista AzMina - Azevedo, Jade Vilar de (2021)
In a patriarchal society every movement of women is a small revolution and all of their acts of content production were a subversion, to a lesser or greater degree of rebellion, of the initial role attributed to them of existing only from the limits of the homes inside. However, for a long period the construction of the resistance lines of the feminists movements and the journalistics representations of women operated under a homogenizing logic. In this context, what women exist in invisibilization when gender analysis is separated from race and class? In order to deconstruct the idea of an alleged homogenization in the woman category, we analyzed in depth the overlap of feminist journalism with intersectionality in the special reports of the digital magazine AzMina. For this, we made a case study of the vehicle observing the practices that reverberate in the construction of the narratives - transforming them into analytical categories and through the intra-category methodology we show how they expose the great intersectional intersections that exist in the category women when gender meets race and class in the analyzes. We observe how the union of these epistemologies in journalistic practice can advance the field in contemplating the complexity inherent to the social, having the possibilities of digital as a tool for promotion and propulsion. We conclude that feminist journalism is an epistemological and practical basis in the way of analyzing and representing any subject through the aegis of gender equity and that intersectionality fits in this context as a necessary praxis so that this equity is not confused with homogeneity and that, therefore, the complexity of the specificities of each reality under analysis is really present in the representations.